INTERDISCIPLINARY APPROACH IN THE STUDY OF MARITAL LAW (STUDY OF THE DETERMINATION OF CHILD COSTODY) - Afriyani, Silfa (Universitas Islam Negeri Raden Fatah Palembang, 2021)
An interdisciplinary approach is an approach that uses various scientific fields in solving a problem. The determination of child custody is usually decided by considering the age of the child. Children who are not yet mumayiz are taken care of by the mother, but when the child is an adult, they are given the choice to live with the mother or father. Through this study, the author examines the determination of child custody according to Islamic law and the Marriage Law and by using psychology and economics. That the custody of children in care must be assigned to the right person. From this paper, the author concludes that according to Islamic law, the determination of child custody takes into account the age of the child. According to Law no. 1 of 1974 concerning Marriage, the determination of child custody before adulthood is decided by a local court judge. In psychology, the determination of child custody takes into account the mental or psychological aspects of the child. Especially in terms of the child's emotional closeness, closer to the mother or father. So that way, the child's condition will be better in living their daily lives and not getting pressure. Meanwhile, by using economics, the determination of child custody is seen from the financial stability of both parents, both from the mother and from the father. Because in carrying out child care requires financially established, so that the needs of children can be met properly. So, in determining child custody, it can not only be seen from the age of the child but can use other considerations. Keywords: Child custody, Mother, Father